2003
DOI: 10.1128/aem.69.1.616-624.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Isolates of Glomus mosseae from Different Geographic Areas Detected by Vegetative Compatibility Testing and Biochemical and Molecular Analysis

Abstract: We detected, for the first time, the occurrence of vegetative incompatibility between different isolates of the arbuscular mycorrhizal fungal species Glomus mosseae. Vegetative compatibility tests performed on germlings belonging to the same isolate showed that six geographically different isolates were capable of self-anastomosing, and that the percentage of hyphal contacts leading to fusions ranged from 60 to 85%. Successful anastomoses were characterized by complete fusion of hyphal walls, protoplasm contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
84
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 56 publications
(77 reference statements)
10
84
2
1
Order By: Relevance
“…Despite the large genetic differences among isolates found within one field, the Canadian isolate was not genetically distant, and, phylogenetically, it fitted into one of the main branches of the population, which suggests either potential gene flow between the Canadian isolate and some of the Swiss population or that the total diversity comprised within a small scale may already account for most diversity on a much larger scale. This finding, however, is in contrast to the findings that geographically distant isolates do not anastomose (40).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Despite the large genetic differences among isolates found within one field, the Canadian isolate was not genetically distant, and, phylogenetically, it fitted into one of the main branches of the population, which suggests either potential gene flow between the Canadian isolate and some of the Swiss population or that the total diversity comprised within a small scale may already account for most diversity on a much larger scale. This finding, however, is in contrast to the findings that geographically distant isolates do not anastomose (40).…”
Section: Discussioncontrasting
confidence: 56%
“…However, to date, experimental studies have only revealed anastomoses between hyphae of spores coming from the same isolate (38,39) and not between isolates of different geographical origin (40). At the scale of our study, the spatial genetic structure of the population shows that exchange of nuclei could not have been frequent enough to cause genetic homogeneity in the population.…”
Section: Discussionmentioning
confidence: 76%
“…Anastomoses were observed in the same germling, where perfect fusions were formed at rates of 51-57 % in F. mosseae, 34-54 % in F. caledonius and 58-68 (Giovannetti et al, 1999). In F. mosseae fusions ranged from 40 to 85 %, depending on isolates (Giovannetti et al, 2003). These results had also been confirmed by studies performed on germlings of Rhizoglomus clarus and Rhizoglomus irregulare (Croll et al, 2009;Cardenas-Flores et al, 2010;De la Providencia et al, 2013).…”
Section: Asymbiotic Myceliumsupporting
confidence: 73%
“…An example of such behavior is found in the ascomycete fungus Rossellinia necatrix , and it appears to be triggered by a single Mendelian factor . Although there is increasing evidence of similar behavior across fungi (Ford et al 1995;Giovannetti et al 2003;Micali and Smith 2003;Iotti et al 2012;Smith and Lafontaine 2013), there is only one example where a gene has been isolated. This example is the vic4 gene of the chestnut blight fungus Cryphonectria parasitica (Ascomycota).…”
Section: Stage Of Rejectionmentioning
confidence: 99%